A Design and Experimental Study of Fog Spraying Into the Greenhouse Roof for Radiation and Relative Humidity Control - Sakapan Klaydokjan; Kamonwan Chucheep; Nathaporn Suwanpayak (My University, 2025)
The objectives of this study were to investigate a design and experimental fog spraying into a greenhouse roof to control the temperature, relative humidity (%RH), radiation intensity (RI), and storage data system, which will support the maximum quality and quantity of vegetarian production. This study is a novel design and experiment concerning a greenhouse model that uses fogging spray on the roof and inside the greenhouse. The automatic control systems are applied with GY-49 sensors, AMT1001 temperature and humidity sensors and DS1307 real time clock module. The experimental results are shown by LCD monitoring using a real-time clock (RTC) from 2.00 a.m. to 8.00 p.m. The percentage difference in radiation intensity inside the greenhouse decreased in the range of 69.58 % to 95.00 %. The maximum temperature inside the greenhouse decreased by $12{}^{\circ} \mathrm{C}$. The temperature variation ratio of fogging is 80 %, while the relative humidity range of 60-97 %RH.
Keywords: Greenhouse Technology and Climate Control